PENGARUH KONSENTRASI KOTORAN ITIK TERHADAP PERTUMBUHAN AZOLLA PINNATA (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2026)
This study aimed to examine the effect of different concentrations of duck manure on the growth of Azolla pinnata and to determine the optimal concentration that promotes the best growth performance without reducing the quality of the cultivation medium. The experiment consisted of five treatments: A1 (without duck manure), A2 (20% duck manure + 80% soil), A3 (30% duck manure + 70% soil), A4 (40% duck manure + 60% soil), and A5 (50% duck manure + 50% soil), with an initial Azolla pinnata density of 200 g/m². The results showed that the application of duck manure had a highly significant effect on the growth rate of Azolla pinnata (P